2023
DOI: 10.21608/pssjn.2023.126473.1183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Program about Authentic Leadership for Head Nurses on Staff Nurses' Resilience and Innovation Behavior

Abstract: Background: Authentic leadership has the power to affect nurses' behavior and job outcomes. As leaders, head nurses can utilize authentic leadership style to favorably influence staff nurses, increasing their creativity, innovative behaviors also facilitating their workplace resilience. Aim: to assess the effect of educational program about authentic leadership for head nurses on staff nurses' resilience and innovation behavior.Research design: Quasi-experimental research design was utilized in the study. Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…This result agreed with Aboelenein, and Mostafa [ 23 ] who studied the effect of an educational program about authentic leadership for head nurses on staff nurses' resilience and innovation behavior among 54 nurse managers at the Tanta International Teaching Hospital and found that the studied nurse managers' knowledge and authentic leadership style levels were low pre-program implementation while, they had higher scores with statistically significant differences post-program implementation. Also, Hassan et al [ 32 ] studied the effect of an authentic leadership training program of head nurses on creativity and motivation of nurse staff among 36 nurse managers at Mansoura University hospital and revealed that there were highly statistically significant differences in a total of head nurses about authentic leadership style knowledge at the three times of the program (pre-test, immediately post-, and three months after the program implementation).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This result agreed with Aboelenein, and Mostafa [ 23 ] who studied the effect of an educational program about authentic leadership for head nurses on staff nurses' resilience and innovation behavior among 54 nurse managers at the Tanta International Teaching Hospital and found that the studied nurse managers' knowledge and authentic leadership style levels were low pre-program implementation while, they had higher scores with statistically significant differences post-program implementation. Also, Hassan et al [ 32 ] studied the effect of an authentic leadership training program of head nurses on creativity and motivation of nurse staff among 36 nurse managers at Mansoura University hospital and revealed that there were highly statistically significant differences in a total of head nurses about authentic leadership style knowledge at the three times of the program (pre-test, immediately post-, and three months after the program implementation).…”
Section: Discussionsupporting
confidence: 87%
“…It's possible due to their active involvement and interest in the program sessions and frequent review of their knowledge. As asserted by Ali et al [ 22 ]; and Aboelenein, and Mostafa [ 23 ] the training programs regarding authentic leadership were considered a new trend in Egyptian nurses' culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study had practical implications for nursing management and leadership development in real‐world health settings. (1) Based on a quasi‐experimental trial (Aboelenein & Mostafa, 2023), the authentic leadership educational program increased head nurses' authentic leadership knowledge and staff nurses' perception of their authentic leadership style after the program implementation. Nursing administrators should identify and promote effective relational leadership.…”
Section: Discussionmentioning
confidence: 99%